Being analog : creating tomorrow's libraries - Crawford, Walt (American Library Association, 1999)
"Walt Crawford, coauthor of Future Libraries: Dreams, Madness, & Reality, offers an alternative model to a simplistic digital future in Being Analog: Creating Tomorrow's Libraries. The always outspoken Crawford challenges popular prognostications, asserting that the complex mix of technologies projects no clear path to the future and that people use technology in unexpected ways." "In today's competitive funding environment, digital dreams of virtual libraries pose the real threat of misguided physical and budgetary planning. Crawford's cogent arguments will help you articulate your own viewpoint to administrators, staff, or users who claim that the virtual library will do it all for less. He explores the roles of libraries and the reasons people use libraries. He helps you make choices among the ever shifting, complex combinations of digital and analog resources." "Being Analog celebrates the remarkable results professional librarianship has achieved in sensibly combining human intelligence and computer power. It points the way to a real world where flexible libraries support today's services and resources while accommodating tomorrow's changes."--Jacket